Asset-based microfinance for microenterprises: Evidence from Pakistan - Bari, F; Malik, K; Meki, M; Quinn, S (University of Oxford, 2021)
We conduct a field experiment offering graduated microcredit clients the opportunity to finance a business asset worth four times their previous borrowing limit. We implement this using a hire-purchase contract; our control group is offered a zero-interest loan. We find large, significant and persistent effects from asset finance contracts: treated microenterprise owners run larger businesses and enjoy higher profits; consequently, household consumption increases, particularly on food and children’s education. A dynamic structural model with non-convex capital adjustment costs rationalises our results; this highlights the potential for welfare improvements through large capital injections that are financially sustainable for microfinance institutions.